2017
DOI: 10.1590/0104-07072017001260016
|View full text |Cite
|
Sign up to set email alerts
|

Forças Que Interferem Na Maternagem Em Unidade De Terapia Intensiva Neonatal

Abstract: Objective: to identify the driving and restrictive forces involved in the maternity process for newborns hospitalized in a neonatal intensive care unit.Method: descriptive and exploratory research, with a qualitative approach, which uses the Force Field Theory as a reference. Ten mothers participated. Data were collected from September to December 2014, through a semi-structured interview, and submitted to content analysis.Results: effective communication, inclusion of the family in care, teamwork, learning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
21

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 15 publications
(26 reference statements)
1
7
0
21
Order By: Relevance
“…As mães, quando não assistidas corretamente, podem apresentar uma distorção da maternidade, principalmente nos casos de nascimento prematuro, em que não houve um preparo para esse acontecimento. Perante essa vivência, o sentimento de impotência aflora, tornando-as frágeis a qualquer situação, sendo assim, torna-se fundamental que o profissional entenda que nem todas as mães conseguem interagir com o RN, outras apenas conseguem observar , custando a reconhecê-lo como seu (9) . Há a necessidade de que os profissionais que atuam na UTIN tenham a capacidade de perceber e entender os sentimentos para que consigam auxiliar os familiares a enfrentarem esse momento da melhor forma, além de promoverem e estimularem um contato direto com o recém-nascido (10) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…As mães, quando não assistidas corretamente, podem apresentar uma distorção da maternidade, principalmente nos casos de nascimento prematuro, em que não houve um preparo para esse acontecimento. Perante essa vivência, o sentimento de impotência aflora, tornando-as frágeis a qualquer situação, sendo assim, torna-se fundamental que o profissional entenda que nem todas as mães conseguem interagir com o RN, outras apenas conseguem observar , custando a reconhecê-lo como seu (9) . Há a necessidade de que os profissionais que atuam na UTIN tenham a capacidade de perceber e entender os sentimentos para que consigam auxiliar os familiares a enfrentarem esse momento da melhor forma, além de promoverem e estimularem um contato direto com o recém-nascido (10) .…”
Section: Discussionunclassified
“…Esses são fatores que podem interferir negativamente na vida dos acompanhantes dos RN hospitalizados, com isso as instituições de saúde precisam investir recursos para promover ambiências acolhedoras, contribuindo na assistência desses familiares. Outro fator importante a ser destacado é a possibilidade de flexibilização das normas e rotinas, uma vez que esta é uma estratégia que oportuniza um cuidado mais efetivo, singular e prazeroso, conduzindo a um cuidado mais subjetivo, comprometido com a autonomia das famílias (9) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Research to identify impulsive and restrictive forces in the process of maternity to newborns hospitalized in the Neonatal Intensive Care Unit showed that comfortable environment for the family, support of the team, educational actions and communication favor the development of the role of the mother and the performance of the team, access to the service, environment of the unit, fear of death, equipment, painful procedures in the child and maternal feelings of strangeness may be obstacles to the mother-child bond (1) .…”
Section: Discussionmentioning
confidence: 99%
“…The survival of newborns in a serious clinical state due to prematurity or other pathologies has been enabled by the complexity, technological and human resources of the Neonatal Intensive Care Unit. This environment is stressful, with specific routines and equipment, which makes it less welcoming, associated with the death and fragility of newborns (1) .…”
Section: Introductionmentioning
confidence: 99%